BLENDED AND ONLINE LEARNING MODELS IN FOREIGN LANGUAGE EDUCATION - Orazimbetov Shing’isbek; Nietullaeva Shaxsanem (Ta'lim innovatsiyasi va integratsiyasi, 2026)
The  rapid  development  of  information  and  communication  technologies  has significantly  transformed  modern  foreign  language  education  and  introduced  new opportunities  for  teaching  and  learning  through  digital  platforms  and  virtual communication tools. This article examines blended and online learning models in foreign  language  education  and  analyzes  their  theoretical  foundations,  practical applications, advantages, and challenges. Blended learning combines traditional face-to-face  instruction  with  online  educational  activities,  while  online  learning  is conducted mainly through internet-based platforms. The study discusses the role of educational technologies, learner autonomy, motivation, communication, and digital competence in successful language acquisition. It also evaluates previous scholarly research  related  to  digital  education  and  language  pedagogy.  The  article  identifies several  advantages  of  blended  and  online  learning  models,  including  flexibility, accessibility, individualized instruction, interactive communication, increased learner participation, and opportunities for lifelong learning. At the same time, the research analyzes challenges such as technical difficulties, lack of internet access, insufficient digital  literacy,  reduced  social  interaction,  and  online  assessment  problems.  The findings demonstrate that blended and online learning models have become essential components of modern foreign language education and should be effectively integrated with  traditional pedagogical  approaches in  order  to  create  flexible, interactive, and learner-centered  educational  environments  suitable  for  the  demands  of  the  modern world.